A política de economia circular da União Europeia e sua integração com os princípios da química verde: uma pesquisa documental - Strinta, Luiz Pedro Tsai (Universidade Federal de São Carlos, 2024)
From the perspective of generating profits, the linear economy has proven inefficient in respecting recycling processes and the reuse of materials, bringing about the need to discuss alternatives to the large amount of waste from discards, often wasted as potential sources of resources and energy. Emerging as a regenerative and restorative alternative, the circular economy (CE) aims to modify the linear activity of the economy by planning closed circuits. This benefits the circularity of materials, capital savings, and consequently reduces the amount of waste discarded. The European Union's document "A new Circular Economy Action Plan" stands as the first major plan for a transition from the linear to the circular model. In view of this, the research aims to conduct documentary analysis on this Action Plan, seeking to investigate how the 12 principles of green chemistry are integrated into the circular economy policy of the European Union (EU). This search aims to map, in a transdisciplinary way, the existence of relationships and gaps between these two development approaches, fostering the creation of multidisciplinary and collaborative systems. As a result of this research, the presence of 7 principles of green chemistry in the circular economy proposed by the EU was identified, observing, however, an alignment of the Plan primarily with the principles of green chemistry that are aligned with the circularity of materials. It is concluded, among other factors, that the EU Action Plan directs greater concern to products manufactured by the industry – those that can be commercialized – rather than to the by-products generated by it, showing the absence of a direct combat against dangerous chemical syntheses. Based on this interpretation, directions for greater integration between the two developmental approaches are proposed, including a review of EU documents and the implementation of an interdepartmental collaboration system. The work also presents a pedagogical proposal that aims to introduce the green chemistry approach to the 3rd year of high school, based on the Curricular Unit (UC) "My Role in Sustainable Development." Using the methodology of the three pedagogical moments and the relationship with the film Wall-e, dialogical interaction is encouraged, also applying an investigative activity that encourages student protagonism, based on a suggestion by the students of new sustainable practices for the laboratory from school.
The European Union's circular economy policy and its integration with the principles of green chemistry: a documentary research
Keywords: Química Verde; Economia Circular; União Europeia; Green Chemistry; Circular Economy; European Union; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS HUMANAS::CIENCIA POLITICA; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO::INSTITUICOES GOVERNAMENTAIS ESPECIFICAS